Words to Sell By An Exploratory Text Analysis of Human Capital Consultant Websites (Journal of Organizational Psychology, 2021)
The present study compares the descriptive language used by boutique, medium and large human capital consulting firms to sell services through their websites. Using computer assisted content analysis of website text (product pages, about us, and FAQ sections) across 123 consulting firms’ websites, resulting in a total of 51,612 words. The findings suggest a strong shared focus on leadership development and assessment across different types of consulting firms. Boutique firms more frequently specialized in surveys and highlighted terms such as health, while larger firms specialized in job fit and leadership. Medium sized firms tend to use the most positive language centered around growth and development (talent, success and effectiveness) while boutique firms show a preference for negative words that create urgency among potential customers urgency (issues, complex). The implications for consulting firms are vast and equally critical. Future research is also needed to explore how human capital consulting firms adapt their website content over time in response to changing internal and external business environments.
Keywords: organizational psychology; qualitative research methods, human capital consulting psychology, consulting, consulting firm, business development